Effects of different types of plants on runoff reduction and suspended solids removal in rain gardens - Li, Chuan; Chen, Lingling; Li, Huan; Miao, Zimei; Yang, Rui; Chu, Lei; Mao, Lingfeng (Journal of Environmental Engineering and Landscape Management, 2023)
This research conducted a series of experiments, determined that 40% is the optimal sand-soil ratio, built three rain gardens, and planted Ilex chinensis Sims and Cynodon dactylon as a key element in the rain gardens. Among them, rain garden A was planted with only Cynodon dactylon for a one-year observation period. Rain gardens B and C, designed as three-year rain gardens, were planted with Ilex chinensis Sims or Cynodon dactylon, respectively. The method of simulating rainwater runoff was used to monitor the rain gardens continuously. The results showed that the total runoff reduction rates of rain gardens A, B, and C were 43%, 53%, and 55%, respectively. The average removal rates of pollutant suspended solids in rain gardens A, B, and C were 94%, 88%, and 87%, respectively, and the suspended solids pollution load reduction rate reached 96%, 94%, and 95%, respectively. This would be significant for future work and as a reference for the selection of plants for rain gardens in China.